2012
DOI: 10.1002/aqc.2225
|View full text |Cite
|
Sign up to set email alerts
|

Morphological diversity and phenotypic plasticity in the threatened British white‐clawed crayfish (Austropotamobius pallipes)

Abstract: ABSTRACT1. Relocation of threatened populations is a common method employed in conservation. However, environmental differences in the new habitat may reduce the survival of relocated populations, while phenotypic plasticity may enhance the likelihood of establishment of relocated populations in their novel environment.2. Conservation of the British white-clawed crayfish (Austropotamobius pallipes; IUCN Red Data List -Endangered) often involves relocation of threatened populations into isolated ponds (Ark Site… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 48 publications
0
19
0
Order By: Relevance
“…Carapaces of juveniles in lotic waters are commonly narrow as they need to resist the water current easily and to find shelter among gravel (Scalici et al, 2010), the preferred substrata at this age stage (Vlach et al, 2009b). Although Curra (1964) mentioned negative allometry in gill growth in crayfish from the genus Austropotamobius, growing gills and other organs need more space resulting in positive allometry of carapace traits (Scalici et al, 2010;Haddaway et al, 2012). On the contrary, we did not found differences in the relative carapace width between sexes, otherwise reported by Streissl andHödl (2002), or Pârvulescu (2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Carapaces of juveniles in lotic waters are commonly narrow as they need to resist the water current easily and to find shelter among gravel (Scalici et al, 2010), the preferred substrata at this age stage (Vlach et al, 2009b). Although Curra (1964) mentioned negative allometry in gill growth in crayfish from the genus Austropotamobius, growing gills and other organs need more space resulting in positive allometry of carapace traits (Scalici et al, 2010;Haddaway et al, 2012). On the contrary, we did not found differences in the relative carapace width between sexes, otherwise reported by Streissl andHödl (2002), or Pârvulescu (2010).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, most observed morphological traits showed a wide range of variability. This variability is an evolutionary strategy based on various genotypes (Brian et al, 2006, Henryon et al, 1989Jones et al, 2000;Lutz and Wolters, 1989) or variations of the same genotype (Ghia et al, 2006) allowing an organism to alter its morphology or behaviour (Haddaway et al, 2012). In the Czech Republic, we should consider more than only one genetic lineage; together with isolated populations from the Danube or Elbe watersheds, a special position is occupied by the stone crayfish population from Luční brook in the Giant Mountains which probably was introduced from the Balkan Peninsula (Pešek, 2013).…”
Section: Figurementioning
confidence: 99%
“…To counter such declines, managed relocations of native crayfish within and outside their natural ranges are often suggested (Olden et al 2010). Such relocations typically target naturally or artificially isolated water bodies to create 'ark' populations protected from range expansion by invasive species (Haddaway et al 2012). Relocations have been conducted in parts of the UK to conserve native white clawed crayfish (Austropotamobius pallipes), which have declined rapidly in range and abundance since the introduction of invasive signal crayfish in the 1970s (Sibley et al 2002;Haddaway et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Such relocations typically target naturally or artificially isolated water bodies to create 'ark' populations protected from range expansion by invasive species (Haddaway et al 2012). Relocations have been conducted in parts of the UK to conserve native white clawed crayfish (Austropotamobius pallipes), which have declined rapidly in range and abundance since the introduction of invasive signal crayfish in the 1970s (Sibley et al 2002;Haddaway et al 2012). Such relocations of native species outside of their home range raises the controversial issue of whether these new populations should be regarded as invasive and hence viewed as a potential threat to the recipient ecosystem (Olden et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Ayrinhac et al, 2004;Haddaway et al, 2012). A strong bias towards the study of crayfish from lotic rather than lentic systems was apparent in the literature retrieved.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%